Investigations of Angular Light Scattering by Complex Atmospheric Particles - Järvinen, Emma (KIT Scientific Publishing, 2016)
This book experimentally investigates the angular light scattering properties of three atmospherically relevant particles: ice crystals, dust particles and secondary organic aerosol particles. Key optical quantities under examination are the near-backscattering depolarisation properties and the angular light scattering function. The main question is how these parameters are related to the particle microphysical properties, such as particle size and complexity.